P16 The combined type-I interferon and neutrophil gene scores identify highly active systemic lupus erythematosus patients and performed better than classical serological markers. (23rd March 2020) - Chasset, François; Ribi, Camillo; Trendelenburg, Marten; Huynh-Do, Uyen; Roux-Lombard, Pascale; Courvoisier, Delphine S; Chizzolini, Carlo
Abstract : Background: In SLE, heterogeneous clinical expression and activity may reflect diverse pathogenic and/or effector mechanisms. We dwelled into SLE heterogeneity by assessing the expression of three gene sets representative of type I interferon (IFN-I), neutrophil-(PMN) and plasmablast-(PB) signatures in a well characterized, multidisciplinary cohort of SLE patients. We further assessed whether individual gene products could be representative of these three signatures. Methods: Whole blood, serum and clinical data were obtained from 140 SLE individuals. Gene expression was assessed by NanoString© technology, using a panel of 37 probes allowing the computation of six IFN-I, one PMN and one PB scores. Protein levels were measured by ELISA. Results: High IFN-I gene expression was found in 45 to 50% of SLE individuals, depending on the score used. All 6 IFN-I scores were significantly associated with active skin involvement and 2 of 6 with arthritis. Interferon-induced GTP-binding protein Mx1 (MX1) correlated with IFN-I score (p<0.0001) and was associated with a similar clinical phenotype. High PMN gene expression was found in 25% of individuals in association with SLE fever, serositis, leukopenia and glucocorticoid use. PB gene expression was highly influenced by immunosuppressant agents with no association with SLE features. The combined IFN-I and PMN gene expression was significantly associated with high disease activity and outperformed anti-dsDNA, anti C1q and complement levels to predict SLE activity. Conclusions: The IFN-I and PMN gene scores segregate with distinct SLE clinical features and their joint expression identify high disease activity. MX1 protein levels perform similarly to IFN-I gene expression. Acknowledgements: Work partially supported by funds provided by a grant from Fondation Fleurette Wagemakers, Sion (Switzerland), by a grant from La Société Académique de Genève (Switzerland). FC was supported by a research travel grant from the French Society of Dermatology and from Institut Servier, Paris (France).